ANALISIS KEPUASAN MAHASISWA TERHADAP PELAYANAN AKADEMIK MENGGUNAKAN METODE ALGORITMA C4.5 (STUDI KASUS: STMIK PRINGSEWU) - -, Oktafianto (244-5567)
This study aimed to analyze the level of satisfaction of students to academic services at STMIK Pringsewu using C4.5 algorithm. There are five aspects are seen in assessing the level of satisfaction, that is tangible, Reability, assurance, responsiveness, and empathy. At STMIK Pringsewu, fifth aspects are not measurable with certainty that the STMIK Pringsewu find it difficult to determine which aspects should be improved. Using C4.5 algorithm method, the authors tried to measure the five aspects, forming a decision tree (decision tree). After doing the calculations manually, then the evidence also use the application, which RapidMiner. From the analysis, it can be seen that the aspect of responsiveness is the most dominant aspect in determining the level of student satisfaction in STMIK Pringsewu.Keywords: satisfaction, C4.5, RapidMiner, decision trees.